Seasonal Dynamics, Record of Ticks Infesting Humans, Wild and Domestic Animals and Molecular Phylogeny of Rhipicephalus microplus in Khyber Pakhtunkhwa Pakistan - Ali, Abid; Khan, Munsif Ali; Zahid, Hafsa; Yaseen, Pir Muhammad; Qayash Khan, Muhammad; Nawab, Javed; Ur Rehman, Zia; Ateeq, Muhammad; Khan, Sardar; Ibrahim, Mohammad (Frontiers in Physiology, 2019)
Although ticks prevalent in various agro-systems of Pakistan are associated with economic losses, information is still missing about the tick’s diversity, hosts they infest, seasonal dynamic and molecular phylogeny of Rhipicephalus microplus in Khyber Pakhtunkhwa (KP) Pakistan. This study for the first time enlisted ticks infesting diverse hosts including human in various regions of KP. A total of 8,641 ticks were collected across north, south and central regions of KP and were morpho-taxonomically categorized into six genera comprising 18 species, R. microplus (n=3,584, 42%), Hyalomma anatolicum (n=2,253, 27%), Argas persicus (n= 1,342, 16%), Hya. impeltatum (n=586, 7%), R. turanicus (n=161, 2%), R. haemaphysaloides (n= 142, 2%), R. annulatus (n=132, 2%), Hae. montgomeryi (n= 123, 1.4%), Hya. marginatum (n=110, 1.3%), R. sanguineus (n=34, 0.4%) and Hae. longicornis (n=31, 0.4%). Ticks infesting wild animals were Amblyomma gervaisi, Amb. exornatum, Amb. latum, Dermacentor marginatus and Hae. indica, while ticks collected from human were R. microplus, R. annulatus, Hya. anatolicum, Hya. marginatum and Hae. punctata. The overall prevalence of tick infesting domestic animals was 69.4% (536/772). Among the animal host, cattle were found highly infested (87.2%, 157/180) followed by buffalos (79%, 91/114), domestic fowls (74.7%, 112/150), goats (68.3%, 82/120), dogs (66.7%, 32/48), horse (61.3%, 49/80), and sheep (16.3%, 13/80). Analysis revealed that tick burden was significantly differed among domestic animals and found high in cattle, followed by buffalos, goats, sheep, domestic fowl, dogs and horses. Seasonal patterns of tick’s distribution showed highest prevalence in July, August and September due to prevailing high temperature and humidity during these months. The phylogenetic analysis of cattle tick R. microplus based on partial mitochondrial cytochrome oxidase subunit I (COX1), 16S ribosomal RNA (16S rRNA) and internal transcribed spacer 2 (ITS2) sequences revealed that R. microplus prevalent in this region belongs to clade C which include ticks originating from Bangladesh, Malaysia and India. Further studies on large scale across the country are necessary to explore molecular and cross breeding aspects at geographical overlapping of various tick species and their associated pathogens that will facilitate designing control strategies as well as awareness against tick infestation in the region.